uji UJI DAYA HASIL BEBERAPA GALUR F9 KETURUNAN PADI BERAS HITAM HASIL PERSILANGAN BAAS SELEM Vs SITU PATENGGANG - Irliana *1; Anugrahwati *2; Uyek Malik Yakop*3 (CROP AGRO, Scientific Journal of Agronomy, 2019)
This exsperiment aimed to determine the yield of F9 lines of black rice from crosses betweenBaas Selem crosses and Situ Patenggang. This experiment was conducted at the Experimental field of the Faculty of Agriculture, University of Mataram in Nyur Lembang Village, Narmada District, West Lombok Regency. The experiment was conducted from April to August 2017, using a Randomized Block Design (RBD) consisting of 13 treatments with three replications to obtain 39 experimental units. The data were analyzed using a 5% level of variance analysis and if there were significant differences it would be tested further by using the Duncan Multiple Range Test (DMRT). The results showed that the F9 lines of black rice still showed a high diversity on growth, yield and yield components. G10 strain is a line with the potential to be developed because it has high grain yield per hectare, which is 6.62 tons / ha which exceeds the yield of the parents (G11 and G12 is not different from the superior variety IR 20 as a control G13, namely IR 20 superior variety. Key words : Black Squeeze Rice, Test Results